Origanum majorana L. polyphenols: in vivo antiepileptic effect, in silico evaluation of their bioavailability, and interaction with the NMDA receptor - Amaghnouje, Amal; Chebaibi, Mohamed; Aldossari, Saeed M.; Ghneim, Hazem K.; Amrati, Fatima Ez-zahra; Es-Safi, Imane; Di Cristo, Francesca; Calarco, Anna; Achour, Sanae; Carta, Fabrizio; Al-Sheikh, Yazeed A.; Aboul-Soud, Mourad A. M.; et al. (Frontiers in Chemistry, 2024)
Epilepsy is a chronic brain disease characterized by repeated seizures and caused by excessive glutamate receptor activation. Many plants are traditionally used in the treatment of this disease. This study aimed to evaluate the bioavailability of a polyphenolic extract obtained from Origanum majorana L. (OMP) leaves, as well as its antiepileptic activity and its potential mechanism of action. We have developed and validated a simple, rapid, and accurate stability-indicating reversed-phase liquid chromatographic method for the simultaneous determination of caffeine and quercetin in rat plasma. The OMP antiepileptic effect was evaluated with pilocarpine-induced seizures, and a docking method was used to determine the possible interaction between caffeic acid and quercetin with the N-methyl-D-aspartate (NMDA) receptor. Both compounds tested showed low bioavailability in unchanged form. However, the tested extract showed an anticonvulsant effect due to the considerably delayed onset of seizures in the pilocarpine model at a dose of 100 mg/kg. The molecular docking proved a high-affinity interaction between the caffeic acid and quercetin with the NMDA receptor. Taken together, OLP polyphenols demonstrated good antiepileptic activity, probably due to the interaction of quercetin, caffeic acid, or their metabolites with the NMDA receptor.